The Processing of Hazardous and Toxic Hospital Solid Waste in Dr. Soetomo Hospital Surabaya - Alvionita Ajeng Purwanti (JURNAL KESEHATAN LINGKUNGAN, 2018)
The increasing number of hospital, increases medical waste in Indonesia. Medical waste is categorized as hazardous and toxic waste as mentioned in Appendix I of Government Regulation number 101 in 2014. The hazardous and toxic waste management in hospital is necessary because if  it is not managed properly can cause injury, environmental pollution, and nosocomial disease. Hazardous and toxic hospital waste management can minimize the effect of it. The purpose of this study was to identify the flow of hazardous and toxic waste management in RSUD Dr. Soetomo according to the regulations. The research type was descriptive observational using secondary data from the installation of environmental sanitation. Data was compared to the Minister of Environment and Forestry Regulation No. P.56 in 2015 about Technical Procedures and Technical Requirements for the Hazardous and Toxic Waste' s Management from Health Service Facilities. The results showed that the management of hazardous and toxic waste in RSUD Dr. Soetomo was fulfill the requirements in the regulation of the Minister of Environment and Forestry No. P.56 of 2015 from the reduction and segregation, storage, transportation and treatment of hazardous and toxic waste.